1999
DOI: 10.1006/jcis.1998.6002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adsorbed Polyaniline on Redox Process on MoO3Surface

Abstract: The effects exhibited by adsorbed conducting polyaniline on the redox process on a molybdenum oxide surface were studied. Thermogravimetric results indicate a 4% polyaniline deposition. Cyclic voltammograms of the adsorbed polymer on MoO3 show that polyaniline exerts remarkable effects on the molybdenum blue oxidation-reduction process, with oxidation and reduction potentials of 0.33 and 0.18 V, respectively. This effect strongly enhances the electrode response, and can be used as an important tool in qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 36 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…(18) are possible. It is probable that the polymeric forms of aniline well known in the literature are created [59][60][61][62] or it undergoes oxidation and the products are strongly adsorbed by carbon. Sun and co-workers [63] showed that the aniline polymerization is possible at the room temperature and it is catalyzed by the presence of H 2 O 2 .…”
Section: The Sources Of Irreversible Adsorptionmentioning
confidence: 99%
“…(18) are possible. It is probable that the polymeric forms of aniline well known in the literature are created [59][60][61][62] or it undergoes oxidation and the products are strongly adsorbed by carbon. Sun and co-workers [63] showed that the aniline polymerization is possible at the room temperature and it is catalyzed by the presence of H 2 O 2 .…”
Section: The Sources Of Irreversible Adsorptionmentioning
confidence: 99%
“…Taking into account these features, polyaniline adsorbed on MoO 3 gave a final product, which was used to electrocatalyze the oxidation of the molybdate ion probe by enhancing the electrode response several times (28).…”
Section: Introductionmentioning
confidence: 99%